Conflitos territoriais entre comunidades tradicionais e concessões florestais: um estudo de caso a partir da Floresta Nacional de Saracá-Taquera, Oriximiná, Pa - NEPOMUCENO, Ítala Tuanny Rodrigues (Universidade Federal do Oeste do Pará, 2021)
This research analyzes the socio-environmental conflicts between riverine communities and the state within the creation of concessions for logging in Saracá-Taquera National Forest in Oriximiná, in northwest of the state of Pará, Brazil. The focus of this research is the community of Acari, which is made up of 40 riverine families. Acari is actively resisting the advancement of logging companies within the forests they traditionally occupy by mobilizing for the recognition of their territorial rights as guaranteed by federal environmental legislation that defines the management of conservation units in which they occupy/reside. Based on empirical analysis and a on a procedural approach of conflict, this paper focuses on three specific objectives: (1) to describe the processes of concession under the Brazilian state and to highlight the social tensions and the role of environmental agencies towards riverine communities within the conservation units; (2) to provide an ethnography of the relationship between Acari and its territory, specially surrounding the communities’ use of the territory, their occupation, and the meanings they attribute to the forest as well as to identify conflicts surrounding concessions for logging under state management models within the Flona; and finally (4) to adopt a “situational analysis” framework (Gluckman, 1987) in the context of the implementation of concessions. This thesis argues that the environmental management framework implicated in both the management model of the Flona and the forest concessions represent serious obstacles for the recognition of territorial rights within riverine communities. Furthermore, environmental agencies think of these rights as obstacles to the objectives behind the creation of conservation units, which are focused predominantly on the exploitation of natural resources on an industrial scale.